Determination of the properties of paramagnetic centers of silicon nitride, under various conditions of heat treatment - Murzalinov, D.O.; Rakymetov, B.A.; Baitimbetova, B.A.; Shaikenova, A.; Muratov, D.A. (Recent Contributions to Physics, 2022)
Investigation of the process of formation of paramagnetic light-emitting particles based on the material. Silicon nitride is widely used as an insulating and passivating layer due to its dielectric properties and due to its high interface barrier. The PECVD method was used to obtain SiNx / SiO2 / Si samples, in which paramagnetic centers were found. A feature of this method is deposition at low temperatures (250-300 °C), which leads to the formation of bonds with hydrogen. Upon further annealing, hydrogen evaporates and dangling particles are formed. An interesting fact is the detection of a signal in weak fields. Long-term furnace annealing in Ar at 800 °C does not change the signal parameters between the third and fourth manganese components; however, the signal in weak fields decreases. Heat treatment at 1100 °C in an Ar medium converts the signal between the third and fourth manganese components and restores the signal in weak fields. The nature of the data corresponds to the signals of the superposition of K and N emitting centers. Depending on the sample annealing temperature, the signal in weak fields is insignificant.